Connective tissue graft plus resin-modified glass ionomer restoration for the treatment of gingival recession associated with non-carious cervical lesions: Microbiological and immunological results - Santamaria, Mauro Pedrine [UNESP]; Casati, Marcio Zaffalon; Nociti Jr., Francisco Humberto; Sallum, Antônio Wilson; Sallum, Enilson Antônio; Aukhil, Ikramuddin; Wallet, Shannon Margaret; Shaddox, Luciana Machion (Springer Nature, 2013)
Objectives: It was previously reported the clinical results of placing subgingival resin-modified glass ionomer restoration for treatment of gingival recession associated with non-carious cervical lesions. The aim of this study was to evaluate the influence of this treatment on the subgingival biofilm and gingival crevicular fluid (GCF) inflammatory markers. Materials and methods: Thirty-four patients presenting the combined defect were selected. The defects were treated with either connective tissue graft plus modified glass ionomer restoration (CTG+R) or with connective tissue graft only (CTG). Evaluation included bleeding on probing and probing depth, 5 different bacteria targets in the subgingival plaque assessed at baseline, 45, and 180 days post treatments, and 9 inflammatory mediators were also assessed in the GCF. Results: The levels of each target bacterium were similar during the entire period of evaluation (p > 0. 05), both within and between groups. The highest levels among the studied species were observed for the bacterium associated with periodontal health. Additionally, the levels of all cyto/chemokines analyzed were not statistically different between groups (p > 0. 05). Conclusion: Within the limits of the present study, it can be concluded that the presence of subgingival restoration may not interfere with the subgingival microflora and with GCF inflammatory markers analyzed. Clinical relevance: This approach usually leads to the placement of a subgingival restoration. There is a lack of information about the microbiological and immunological effects of this procedure. The results suggest that this combined approach may be considered as a treatment option for the lesion included in this study. © 2012 Springer-Verlag.
Keywords: Cementoenamel junction; Gingival recession/surgery; Glass ionomer cement; Surgical flap; Tooth abrasion